Heterogeneous expression of serine protease inhibitor maspin in ovarian cancer - Bauerschlag, D. O.; Habermann, M.; Weimer, J.; Meinhold-Heerlein, I.; Hilpert, F.; Weigel, M.; Bauer, M.; Mundhenke, Christoph; Jonat, W.; Maass, N.; Schem, Christian (Anticancer Research, 2010)
Ovarian cancer (OC) is a disease with poor prognosis, and molecular markers are needed to improve understanding of disease progression and resultant treatment. Only limited data concerning the expression of maspin, a serine protease inhibitor, in ovarian cancer (OC) are available. This study investigates the prognostic value of maspin expression (ME) in various OC cell lines and clinical tissue specimens from OC patients. Patients and Methods: Tumour purified mouse anti-human maspin monoclonal antibody was applied to tissue specimens from 87 OC patients. ME was recorded by an immunoreactive score, which was correlated with grading, stage, histopathological subtypes and overall survival. Additionally ME was evaluated in established ovarian cancer cell lines (HEY, SKOV3, OVCAR3/8) and paclitaxel- and docetaxel-resistant HEY cells by QRT-PCR. Results: There was significant correlation between cytoplasmatic ME and overall survival (p<0.05). OC patients with high levels of ME had a median survival of 28 vs. 57 months for those with low levels. Significant differential ME was detected between benign, borderline ovarian lesions and OC, as well as among different tumour gradings. Normal ovarian epithelial cells expressed less maspin than ovarian cancer cells as measured by QRT-PCR. Docetaxel-and paclitaxel-resistant ovarian cell lines showed an even higher level of ME, suggesting an unfavourable role of ME in OC cell lines. Conclusion: Maspin is expressed differentially in OC, and low expression levels of maspin are correlated with a longer survival.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Maspin expression; Ovarian cancer; Survival